Does Carbon Dioxide Have a Significant Dynamic Effect on Agricultural Productivity in Indonesia? - Aliasuddin, Aliasuddin; Rahmi, Nanda; Sakhi, Fathina Almahira (International Journal of Energy Economics and Policy, 2026)
This study investigates the dynamic influence of carbon dioxide (CO₂) emissions, labor, and capital formation on agricultural productivity in Indonesia, utilizing annual data from 2000 to 2023 and employing an Autoregressive Distributed Lag (ARDL) model. The coefficient of carbon dioxide has no significant dynamic effect on the agricultural productivity in Indonesia in the short run. Meanwhile, labor and capital have dynamic and significant effects on agricultural productivity in the short run. However, carbon dioxide, labor, and capital have no significant long-term effects on agricultural productivity. Furthermore, labor exhibits cyclical and inconsistent effects, reflecting seasonal employment patterns and skill limitations, whereas capital consistently has a positive impact on productivity through mechanization and technological advancements.